Limnology in Argentina: an historical account - López, Hugo Luis (1994)
This short review includes major books, articles and episodes concerned with studies on inland waters that have aífected the development of limnology in Argentina. Earlier accounts o( the history of limnology, though based on various other criteria, are by Popovici & Righi (1 948); Olivier (1961a); Marini et al. (1963); Di Persia & Neiff (1973); Schnack (1984); López (1988); Drago (1990); Gabellone & Casco (1 992). In this account we adopt the proposal of Di Persia & Neiíf (1973) who divided their historical analysis into three periods: (1) an early period of protolimnologists; (2) a period previous to the present times, subdivided into a first stage from 1900 to 1938 and a second stage from 1938 to 1962; (3) a pcriod of integrated research.